Shifting The Paradigms Of Agricultural Extension In India: An Overview (Agro-Science Letters, 2026)
In scientific discourse, paradigms represent coherent frameworks  comprising theoretical assumptions, methodological conventions, and  evaluative criteria that collectively define the boundaries and standards of  a discipline. Within the field of agricultural extension in India, four distinct  paradigmatic orientations have emerged and evolved over time. The earliest  of these, rooted in the colonial era and later revived during the 1970s through  the Training and Visit (T&V) system across Asia, was Technology Transfer  — characterized by a top-down, persuasive, and paternalistic approach to  delivering research-based recommendations aimed at boosting farm output  through largely conventional models. This was followed by the Advisory  Work paradigm, which introduced a more interactive and participatory  dimension into extension delivery, emphasizing farmer training, collective  organization through self-help groups, and the introduction of farmer  field schools and university-based extension frameworks. The most recent  evolutionary phase has been marked by a turn toward Facilitation for  Empowerment, an approach premised on educational and participatory  modes of engagement that foreground horizontal communication, group based problem solving, and farmer-centred methodologies. This review  demonstrates that each paradigmatic transition contributed incremental  insights to extension practice — beginning with rural development goals  and culminating in a dynamic, empowerment-oriented system designed to  foster sustainable agricultural transformation.
Keywords: Paradigms; Technology Transfer; Training and Visit System; Facilitation for Empowerment